Intensity of Price and Volatility Spillover Effects in Asia-Pacific Basin Equity Markets - Sazali Abidin; Krishna Reddy; Chun Zhang (Australasian Accounting, Business and Finance Journal, 2015)
This paper investigates the intensity of price and volatility spillover effects in five major stock markets within the Asia Pacific basin region with a particular emphasis in the spillover effects between Australia and China. VAR(5) model is used for measuring the return spillover while AR/VAR model with exogenous variables is employed for measuring the effects of same day returns on return spillover. .In modelling the volatility spillover, we employ AR/GARCH model which also incorporates the same day effects. Results of both return and volatility spillover provide evidence that there are significant spillover effects across different markets in the Asia-Pacific region and as well as between Australia and China. This study also provides support to the view that a market is most affected by other markets that opens/closes just before it. The main contribution of this paper is the confirmation of spillover effects between markets in the region, in particular, the interdependence between Australia and China which may have evolved only recently and thus have received relatively little research attention to date.